Doxorubicin induced dilated cardiomyopathy in a rabbit model: An update - Gava, Fábio N. [UNESP]; Zacché, Evandro [UNESP]; Ortiz, Edna M.G. [UNESP]; Champion, Tatiana [UNESP]; Bandarra, Marcio B. [UNESP]; Vasconcelos, Rosemeri O. [UNESP]; Barbosa, José C. [UNESP]; Camacho, Aparecido A. [UNESP] (Elsevier, 2013)
Dilated cardiomyopathy (DCM) is characterized by chamber dilation and cardiac dysfunction. Because of the poor prognosis, models are needed for the investigation of and development of new therapeutic approaches, as well as stem cell therapy. Doxorubicin (DOX), used as chemotherapeutic agent, is reported to be cumulative cardiotoxic causing DCM. The aim of the study was to investigate the onset of systolic dysfunction using echocardiography in rabbits receiving two different doses of DOX (1. mg/kg twice a week and 2. mg/kg once a week). Twenty rabbits were treated with doxorubicin in two different doses for 6. weeks and compared with a control group treated with NaCl 0.9%. The effect of doxorubicin on the myocardium was investigated with histological analysis and scanning electron microscopy of left ventricle (LV), as well as in the interventricular septum (IVS) and right ventricle (RV). The results showed a high mortality rate for rabbits receiving 2. mg/kg once a week. A significant reduction in systolic function was present in animals treated with DOX after 6. weeks, with decreased ejection fraction and shortening fraction. Histology and electron microscopy revealed vacuolization, intracytoplasmic granulation, necrosis and interstitial fibrosis in LV, as well as in the IVS and RV. Doxorubicin induced changes are present in the LV, RV and IVS, and the administration at the dose of 1. mg/kg twice a week for only 6. weeks is safe and sufficient to induce DCM in rabbits. © 2012 Elsevier Ltd.
Keywords: Doxorubicin; Echocardiography; Histopathology; Rabbits; Scanning electron microscopy; doxorubicin; animal cell; animal experiment; animal model; cardiotoxicity; cell death; cell degeneration; cell inclusion; cell vacuole; congestive cardiomyopathy; controlled study; echocardiography; fibrosing alveolitis; heart contraction; heart ejection fraction; heart left ventricle; heart ventricle septum; histopathology; lymphocytic infiltration; male; mortality; nonhuman; rabbit; scanning electron microscopy; systolic dysfunction; Animals; Cardiomyopathy, Dilated; Disease Models, Animal; Dose-Response Relationship, Drug; Heart; Male; Microscopy, Electron; Microscopy, Electron, Scanning; Myocardium; Stroke Volume; Animalia; Oryctolagus cuniculus